Large Bayesian VARs - Marta Bańbura; Domenico Giannone; Lucrezia Reichlin (European Central Bank (ECB), 2008)
This paper shows that Vector Autoregression with Bayesian shrinkage is an appropriate tool for large dynamic models. We build on the results by De Mol, Giannone, and Reichlin (2008) and show that, when the degree of shrinkage is set in relation to the cross-sectional dimension, the forecasting performance of small monetary VARs can be improved by adding additional macroeconomic variables and sectoral information. In addition, we show that large VARs with shrinkage produce credible impulse responses and are suitable for structural analysis.
Keywords: C11; C13; C33; C53; 330; Bayesian VAR; forecasting; large cross-sections; Monetary VAR; Mathematik; VAR-Modell; Prognoseverfahren